2011
DOI: 10.1038/nn.2925
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic nucleus stimulation reverses mediofrontal influence over decision threshold

Abstract: It takes effort and time to tame one's impulses. Although medial prefrontal cortex (mPFC) is broadly implicated in effortful control over behavior, the subthalamic nucleus (STN) is specifically thought to contribute by acting as a brake on cortico-striatal function during decision conflict, buying time until the right decision can be made. Using the drift diffusion model of decision making, we found that trial-to-trial increases in mPFC activity (EEG theta power, 4–8 Hz) were related to an increased threshold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

77
643
8
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 629 publications
(731 citation statements)
references
References 38 publications
77
643
8
3
Order By: Relevance
“…The increase presumably reflects a ramping of beta activity with temporal expectancy of the imperative cue (Androulidakis et al, 2007), and is similar to that reported after nogo imperative cues (Kühn et al, 2004). In the latter case, the beta power increase was interpreted as evidence of an active inhibitory process, consistent with current views that afford the STN a critical role in motor inhibition (Frank et al, 2007;Ray et al, 2009Ray et al, , 2012Forstmann et al, 2010;Cavanagh et al, 2011). By analogy, the power increase before the imperative cue in the current paradigm could relate to the inhibition of a prepotent response to the imperative cue.…”
Section: Discussionsupporting
confidence: 81%
“…The increase presumably reflects a ramping of beta activity with temporal expectancy of the imperative cue (Androulidakis et al, 2007), and is similar to that reported after nogo imperative cues (Kühn et al, 2004). In the latter case, the beta power increase was interpreted as evidence of an active inhibitory process, consistent with current views that afford the STN a critical role in motor inhibition (Frank et al, 2007;Ray et al, 2009Ray et al, , 2012Forstmann et al, 2010;Cavanagh et al, 2011). By analogy, the power increase before the imperative cue in the current paradigm could relate to the inhibition of a prepotent response to the imperative cue.…”
Section: Discussionsupporting
confidence: 81%
“…For example, the diffusion model has been used to study implicit racial associations (Klauer, Voss, Schmitz, & Teige-Mocigemba, 2007), effects of aging on brightness discrimination (e.g., Ratcliff, Thapar, & McKoon, 2006), practice effects on lexical decisions (Dutilh, Krypotos, & Wagenmakers, 2011), the effect of attention deficit hyperactivity disorder on a conflict control task (Metin et al, 2013), and the effect of alcohol consumption on movement detection (van Ravenzwaaij, Dutilh, & Wagenmakers, 2012). Response time models have also been applied to inform the analysis of brain measures (e.g., Cavanagh et al, 2011;Forstmann et al, 2008;Mulder, Van Maanen, & Forstmann, 2014;Ratcliff, Philiastides, & Sajda, 2009). …”
Section: Cognitive Models Of Response Time Datamentioning
confidence: 99%
“…Historically, null-hypothesis significance tests on estimated parameters were standard (Ratcliff, Thapar, & McKoon, 2004). However, based on growing skepticism over such techniques (e.g., Wagenmakers, 2007), model-selection based methods (Donkin, Brown, Heathcote, & Wagenmakers, 2011), and inference based on posterior distributions is now common (Cavanagh et al, 2011).…”
Section: Threats To the Validity Of Cognitive Modelsmentioning
confidence: 99%
“…A separate study with a similar behavioral paradigm was performed recently with local field potential (LFP) recordings from the DBS lead in the STN (Cavanagh et al, 2011). Compared with low-conflict trials, high-conflict trials exhibited lower theta power within 250 ms and higher delta band power 750 ms after stimulus presentation.…”
Section: What Does Stn Spiking Encode?mentioning
confidence: 99%